Relasi Tasawuf dan Pendidikan Karakter dalam Pemikiran Hamka - Dodi Remaja (Lembaga Yasin AlSys, 2026)
The character crisis in the modern era demands Islamic education that not only develops students’ intellectual intelligence but also strengthens their spiritual, moral, and social maturity. This study aims to analyze the relationship between Sufism and character education in Hamka’s thought and to explain the relevance of Hamka’s modern Sufism as a foundation for character development in Islamic education. This study employed a qualitative approach using a literature review method. Data were obtained from Hamka’s works, particularly Tasawuf Modern, as well as various scholarly sources relevant to Sufism, character education, and Islamic education. The data were analyzed using content analysis through the processes of identifying, interpreting, and synthesizing the principal concepts in Hamka’s thought. The findings show that Sufism in Hamka’s thought constitutes a process of spiritual purification directed toward the formation of noble character. The values of ikhlas, sabar, qana’ah, tawakal, zuhud, syukur, muhasabah, and tawaduk serve as important foundations for character education. The relationship between Sufism and character education is integral, in that Sufism functions as the basis for inner development, whereas character education constitutes the practical manifestation of Sufi values in actual behavior. This study concludes that Hamka’s modern Sufism is relevant as a foundation for integrative, humanistic, and contextual Islamic character education in addressing the moral challenges of modern society. These findings contribute to the development of a spirituality-based concept of character education and strengthen the theoretical foundation for applying Sufi values in Islamic education. Keywords: Modern Sufism; Character Education; Hamka’s Thought; Islamic Education; Noble Character